Crisis Neopatrimonialism: Russia's new political economy and the 2018 World Cup - Wolfe, Sven Daniel; Müller, Martin (My University, 2018)
The economic crisis since 2010 has affected Russia’s political economy by reducing the income available to fund political loyalty—the key mechanism of neopatrimonialism. Through an investigation of key infrastructure development projects, we examine how this crisis has affected the preparations for the 2018 Football World Cup. In so doing we introduce the concept of crisis neopatrimonialism, referring to the political and economic adaptations of a neopatrimonial system in response to economic crisis. Our research uncovered three major adaptations of neopatrimonialism in the context of World Cup preparations: a retreat of private money and concomitant rise in public funding, a reordering of favored elites, and higher costs of loyalty.